(untitled) (Journal of Shaheed Suhrawardy Medical College, 2013)
Background: Nephrotic syndrome causes a great morbidity and mortality among the children. Objective: The purpose of the present study was to compare the biochemical and hematological parameters and their prognostic value in steroid resistant (SRNS), frequent relapse and steroid dependent (FRNS+SDNS) and infrequent relapse (IFRNS) groups. Methodology: A prospective study of 43 children with idiopathic nephrotic syndrome (INS) selected randomly out of 480 children admitted with the disease at Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka from January 2003 to January 2005. There were 24 steroid sensitive nephrotic syndrome (SSNS) and 19 steroid resistant nephrotic syndrome (SRNS), of SSNS group 13 were infrequent relapse (IFRNS) and 11 were frequent relapse steroid dependent (FRNS+SDNS). Result: SRNS has low serum total protein (STP), albumin and hemoglobin compared to SSNS (P<0.01, P<0.001). SRNS also has high cholesterol, creatinine and urinary total protein (UTP) than SSNS (P<0.01, P<0.001). Higher difference was observed between SRNS and IFRNS (P<0.001). High serum cholesterol, UTP and low hemoglobin were found in FRNS+SDNS compared to IFRNS (P<0.01, P<0.05). Conclusion: STP, albumin, creatinine were equally low in SRNS and FRNS+SDNS. DOI: http://dx.doi.org/10.3329/jssmc.v5i2.20764 J Shaheed Suhrawardy Med Coll 2013;5(2):95-98